2010
DOI: 10.1186/1824-7288-36-77
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality amongst infants of diabetic mothers admitted into a special care baby unit in Port Harcourt, Nigeria

Abstract: BackgroundInfants born to diabetic women have certain distinctive characteristics, including large size and high morbidity risks. The neonatal mortality rate is over five times that of infants of non diabetic mothers and is higher at all gestational ages and birth weight for gestational age (GA) categories.The study aimed to determine morbidity and mortality pattern amongst infants of diabetic mothers (IDMS) admitted into the Special Care Baby Unit of University of Port Harcourt Teaching Hospital.MethodsThis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
64
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 28 publications
14
64
9
Order By: Relevance
“…This fi ndings is almost similar to the fi ndings of another study 6,7,8 . But our study diff ers from Begum A et.al 9 .…”
Section: Discussionsupporting
confidence: 81%
“…This fi ndings is almost similar to the fi ndings of another study 6,7,8 . But our study diff ers from Begum A et.al 9 .…”
Section: Discussionsupporting
confidence: 81%
“…Peace I Opara et al reported a caesarean section rate as 74.3%. 8,9 The mean birth weight in our study was 2824 gm among the GDM meal plan group while in the group on insulin therapy it was 2919 gm. In a study by Girish Gopal et al the mean birth weight observed was 3.06±0.82kgs.…”
Section: Discussionmentioning
confidence: 97%
“…There were no major congenital anomalies in their study. 9 Deorari AK et al in their study found that 15% babies were preterm and 20% were low birth weight (less than 2500 g). 10 17% were large-for-dates (LFD) and 6.2% were small-for-dates (SFD).…”
mentioning
confidence: 99%
“…These low birth weight babies (LBW) also have high tendency to develop hypoglycemia during early periods of life. 12 The study was designed to find out the incidence of IDM among LBW babies and to evaluate the status of blood glucose level in those babies within first 48 hours of age.…”
Section: Introductionmentioning
confidence: 99%